Reversible and "fingerprint" fluorescence differentiation of organic amine vapours using a single conjugated polymer probe1. Issue 12 (28th March 2015) - Fu, Yanyan; Yao, Junjun; Xu, Wei; Fan, Tianchi; He, Qingguo; Zhu, Defeng; Cao, Huimin; Cheng, Jiangong
<x xml:space="preserve">Abstract</x> By embedding multiple reactive groups onto one polymer, an ultrasensitive and reversible fluorescent probe for different organic amines vapour has been reported.